Soot Filtration Recent Simulation Analysis in Diesel Particulate Filter (DPF) - M.A., Mokhri; N.R., Abdullah; S.A., Abdullah; S., Kasalong; R., Mamat (Elsevier Ltd, 2012)
Diesel Particulate Filter (DPF) is one of the prominent after-treatment devices invented to reduce particulate matter (PM) emission from diesel engines. With the latest emission standard becoming more stringent in order to maintain the environment sustainability, the study on soot filtration phenomenon occurring inside the DPF is crucial. In addition, the advancement of computer technology contributes to better understanding by simulating the soot filtration process. The flow pattern and velocity of exhaust gas are analyzed in order to examine the flow path and thus the area for soot deposition inside the channel. After a certain soot deposition time, a pressure drop is created and different patterns are observed during initial stage, soot loading and regeneration steps. The soot cake formation also affects the efficiency and pressure drop of the DPF. Hence, these understanding can be adopted for advanced research in optimizing the DPF design and efficiency.